Developing Science Teaching Material to Increase Elementary Students’ Science Process Skill - Rahayu, Ai Hayati; Syarifudin, Bunyamin Faisal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
Mastering science process skill is very beneficial in problem solving process. Thisresearch aimed to develop teaching materials such as science process skill-based textbooks on energy and its changes. The method used in this research was research and development, by using the 4D design, which include define, design, develop, and disseminate. Research and development method were used to produce a product and to test its efficiency. The result showed that the learning material fulfill the assessment criteria. The mean validation result of textbook showed a number of 3.58 indicated as a good category. Based on T test, it was proven that the use of textbooks is indeed influential towards the development of students’ science process skill.